Rahasia Bandung, Jejak leluhur dari Fujian sampai ke tanah Parahyangan. (The secret ancestor artefacts in Bandung, from FuJian down to Priangan) - Tan Soey Beng (Fakultas Seni Rupa dan Desain ITB, 2015)
Although Tan Nyim Tjoy as a chinese village master (wijkmeester) of Citepus in Bandung in the year of 1914 has been mention alot in the studies of chinese history in Bandung, his grave has never been found. Nevertheless Sim Cong alley and Sim Cong primary school are well known in that area. The question is whether they are the same person pronounced in different dialect. To solve that problem a study was conducted to find out some answers in his artefacts that could be found in the tombstone of his relatives or elsewhere and orally as well as written notes of his decendants. Results showed that the question can not be answered but Tan Sim Tjong allegedly was the Chinese village master and known to his descendents by that name, on the other hand official records wrote his name as Tan Nyim Tjoy, possibly the same person. His ancestor could be traced back to Nan Jing village in Fu Jian province who migrated to Southeast Asia. Tan Hwie Tjeng was recorded as the first known ancestor that settled down in Batang in central Java for several generations before moving westward to Cirebon and Jamblang, his descendents became prominent bussinessmen and leaders in that area and gained a substantial wealth. Tan Sim Tjong dan Tan Sim Sioe moved from Cirebon to Bandung and settled down in Citepus as